P-B32 cGMP production, characterization, and formulation of IHV01 drug product, the Full Length Single Chain gp120- CD4 (FLSC) chimera formulated in Aluminum Phosphate. (January 2016) - Prado, Ilia; Bobb, Kathryn; Zhang, Wenlei; Schwartz, Jennifer; Cristillo, Anthony; Livesay, Jessica; Weiss, Deborah; Galmin, Lindsey; Treece, James; Pal, Ranajit; Jenkins, Michael; Gustines, Robert; et al.
Abstract : The FLSC vaccine is fusion protein consisting of a modified full length gp120 protein, derived from HIVBaL, and the first 2 domains (D1D2) of human CD4, genetically fused via a 20 amino acid linker. Experiments in Rhesus macaques demonstrated protection using HEK 293 cell produced rhesus FLSC. A master cell bank expressing human FLSC was prepared from G293H, a derivative of HEK-293 cell that grows in suspension, using the GPEx retrovector transduction system. Tumorgenicity studies performed in athymic nude mice demonstrated that the FLSC MCB generated tumors at the same rate as the HEK-293 cell line available from ATCC. Bioreactor production rates were consistent from the 2 L to the 200 L scale, yielding approximately 1 g/L after downstream purification. Drug substance was predominately monomeric, and expressed the expected CD4 induced structure. A drug product formulation with aluminum phosphate was developed. Potency studies demonstrated a significant relationship between the dose of the FLSC/Alum (IHV01) and the induction of the desired CD4i directed immune response. Immunogenicity studies performed in rhesus macaques showed that the FLSC/Alum formulation induced antibodies directed to CD4i epitopes and mediated ADCC activity while T cell responses were modest. A repeat-dose (N+1) toxicity study in rabbits demonstrated that the majority of the effects observed were attributed to general inflammation occurring with intramuscular vaccine administration and/or an active immune response towards the antigen. An immunotoxicity study in cynomolgus monkeys showed no deleterious autoimmune effects directed to CD4. A phase 1 clinical trial with IHV01 is anticipated to start in September, 2015.